PENGEMBANGAN KOLEKSI DI UPT PERPUSTAKAAN POLITEKNIK NEGERI SRIWIJAYA - Agil Adzzani, Kemas Muhammad; Mulyadi, Mulyadi (Jurnal Multidisipliner Bharasumba, 2025)
The development of library collections is one of the key aspects in supporting academic activities in higher education institutions. The Politeknik Negeri Sriwijaya Library strives to continuously improve its collection to support the quality of education and research. This article aims to evaluate the development of library collections at Politeknik Negeri Sriwijaya by assessing the methods used in collection acquisition, the challenges faced, and the impact of collection development on the academic community. The results of the study indicate that the development of both physical and digital collections at the Politeknik Negeri Sriwijaya Library is increasingly aligned with curriculum needs and technological advancements. However, several challenges remain, including budget constraints, collection management, and the optimal utilization of technology. This article also provides recommendations for improving the collection management system to make it more efficient and inclusive.